Myofascial force transmission in sacroiliac joint dysfunction increases anterior translation of humeral head in contralateral glenohumeral joint - Joseph,L.L. (Polskie Towarzystwo Lekarskie, Oddzial Regionalny w Olsztynie, Okregowa Warminsko-Mazurska Izba Lekarska, 2015)
© 2014 Warminsko-Mazurska Izba Lekarska w Olsztynie. Published by Elsevier Urban and Partner Sp. z o.o. All rights reserved. Introduction Posterior and anterior oblique muscle slings contribute to the force closure mechanisms that provide stability to sacroiliac joint. These global muscle slings consist of myofascial network of fascia, muscles and tendons from global muscles. It links the lumbopelvic region to other joints of musculoskeletal system especially the contralateral glenohumeral joint (GHJ). Any sacroiliac joint dysfunction (SJD) may likely disrupt the force transmission across the oblique slings and it can affect the contralateral GHJ. Aim The current study aims to investigate the effects of SJD on the contralateral GHJ. Material and methods An experimental study is designed recruiting 20 participants with SJD and 20 healthy participants as matched controls to test the hypothesis that SJD may cause excessive anterior translation of humeral head (ATHH) in contralateral GHJ. Using real time ultrasonography, resting position of humeral head (RPHH), ATHH and posttranslation distance of humeral head (PDHH) are compared between the GHJs among participants with SJD and the matched controls. Paired sample t-test and independent sample t-test are used to analyze the data. Results and discussion The paired sample t-test result showed statistically significant increase in ATHH (P = 0.03) and PDHH (P = 0.01) in contralateral GHJs among participants with SJD. The independent sample t-test showed a significant increase in RPHH (P = 0.01) and PDHH (P = 0.01) in SJD participants when compared to matched controls. Conclusion SJD contributes to excessive ATHH in the contralateral GHJ. This may occur due to altered myofascial force transmission across oblique sling muscles.